1999
DOI: 10.1007/pl00006616
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Dibenzo-p-Dioxins (PCDDs) and Dibenzofurans (PCDFs) in Muscle and Eggs of Salmonid Fishes from the Great Lakes

Abstract: Concentrations of polychlorinated dibenzo-p-dioxins (PCDDs) and dibenzofurans (PCDFs) were measured in dorsal muscle and eggs of coho salmon, lake trout, and chinook salmon collected from Lakes Superior, Michigan, and Huron (Michigan waters). Absolute and relative concentrations of PCDDs and PCDFs varied among sampling locations (inter- and intralake) and fish species. Fish collected from Bay City (Saginaw Bay) contained the greatest concentrations of PCDDs and PCDFs both in muscle and eggs. Among the three fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Investigations carried out by Loonen et al [17] indicated very low dietary absorption efficiencies for PCDD/Fs in general, and the absorption of penta‐ and hexachlorinated dibenzo‐ p ‐dioxins and dibenzofurans was more efficient than the absorption of tetra‐, hepta‐, and octachlorinated dibenzo‐ p ‐dioxins and dibenzofurans. On the other hand, absorption of hepta‐ and octachlorinated dibenzo‐ p ‐dioxins and dibenzofurans in fish is not fully inhibited because of their extreme structural and physicochemical properties, because they were actually among the main congeners in the salmonid fishes of the Great Lakes [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations carried out by Loonen et al [17] indicated very low dietary absorption efficiencies for PCDD/Fs in general, and the absorption of penta‐ and hexachlorinated dibenzo‐ p ‐dioxins and dibenzofurans was more efficient than the absorption of tetra‐, hepta‐, and octachlorinated dibenzo‐ p ‐dioxins and dibenzofurans. On the other hand, absorption of hepta‐ and octachlorinated dibenzo‐ p ‐dioxins and dibenzofurans in fish is not fully inhibited because of their extreme structural and physicochemical properties, because they were actually among the main congeners in the salmonid fishes of the Great Lakes [18].…”
Section: Resultsmentioning
confidence: 99%
“…Chem. 23,2004 P. Isosaari et al not fully inhibited because of their extreme structural and physicochemical properties, because they were actually among the main congeners in the salmonid fishes of the Great Lakes [18]. The lower accumulation efficiencies of PCDD/Fs as compared with PCBs were expected based on the results of previous studies [19].…”
Section: Accumulation Efficienciesmentioning
confidence: 98%
“…Other studies have shown that water can be a major pathway for accumulation of PCDD/F congeners [14]. In our study, fish were kept under standard aquaculture conditions and were fed environmentally relevant concentrations of TCDD based on data obtained for forage fish from the North American Great Lakes [1,2,20]. Mass balance studies, both in the laboratory and field, indicate that in larger predatory species, the primary vector of accumulation is via diet [2,3].…”
Section: Resultsmentioning
confidence: 99%
“…These observations make it necessary to investigate the accumulation and effects of PCDD/F congeners during long-term exposures at ecologically relevant concentrations. In our study, fish were kept under standard aquaculture conditions and were fed environmentally relevant concentrations of TCDD based on data obtained for forage fish from the North American Great Lakes [1,2,20]. Because no effect was found on growth or reproductive status of the fish in this study, the accumulation characteristics observed for these fish should be representative of those that would be expected to occur in the environment.…”
Section: Resultsmentioning
confidence: 99%
“…Fish are often exposed to relatively small concentrations of polychlorinated dibenzo‐ p ‐dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and similar compounds but can accumulate these compounds to concentrations that can have adverse effects on the fish or on predators that consume them [1]. In ecological risk assessment, ability to predict tissue‐specific concentrations of PCDDs and PCDFs (PCDD/Fs) that could be accumulated during long‐term exposures is important.…”
Section: Introductionmentioning
confidence: 99%